Incidence of Postoperative Nausea and Vomiting in Dr. Hasan Sadikin General Hospital Bandung Period May to October 2013 - Aisyah Ummu Fahma; Iwan Fuadi; Jimmy Setiadinata (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Postoperative nausea and vomiting (PONV) is common complication in patients undergoing surgery with anesthesia. The incidence of PONV is ranging between 20% and 30%. Despite many other studies about PONV in other regions, the descriptive data about PONV in Dr. Hasan Sadikin General Hospital Bandung is still unknown. The aim of this study was to determine the incidence of PONV in Dr. Hasan Sadikin General Hospital Bandung.Methods: This descriptive study used a cross-sectional method. As many as 521 medical records in Departement of Anesthesiology and Intensive Care Dr. Hasan Sadikin General Hospital Bandung from May 5th to October 31st 2013 were reviewed. The subjects were taken by using total sampling technique. Data collected were gender, age, type of surgery, type of anesthesia, duration of surgery, administration of nitrous oxide, and administration of neostigmine.Results: Of 521 patients,the incidence of PONV was 20.5%. Female had higher incidence of PONV than male. Postoperative nausea and vomiting was the most frequent in the age category 6−20 years old. The Ear Nose and Throat (ENT) surgery was revealed as surgery with the highest incidence. Regional anesthesia had a higher incidence than general anesthesia. Operation lasting 181−210 minutes was considered as category which PONV mostly occured. Patients receiving nitrous oxide were more likely to experience PONV, and patients who were given neostigmine as muscle relaxant had lower incidence of PONV compared to those who were not.Conclusions: The incidence of PONV was similar to the study presumed earlier and this may influenced by many factors including patients, surgical, and aenesthtical factor. [AMJ.2017;4(1):58–63]DOI: 10.15850/amj.v4n1.1022